DESENVOLVIMENTO DAS TÉCNICAS PSICOPOLÍTICAS DE PODER E A AMEAÇA AOS DIREITOS DA PERSONALIDADE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to carry out a panoramic study on the evolution of power techniques and the formation of psychopolitics, analyzing their reflexes on the rights of personality. For this, the study uses the hypothetical-deductive method, a qualitative approach, of a basic nature, with an explanatory and exploratory objective, fundamentally based on the bibliographic research of the objects under study. The article was developed in sessions: initially, considerations about personality rights, their conceptualization and recognition in the positive international and Brazilian order throughout history are presented; then, an overview is drawn on the development of power techniques and the formation of psychopolitics; bringing together, in the sequence, a discussion about the reflexes of the narrated social scenario on the rights of the personality and, especially, on the violations to individuals, whether in their physical, psychological or moral dimension, presenting, finally, final considerations on the theme addressed.